Pengaruh Model Case Based Learning (CBL) Terhadap Hasil Belajar Mahasiswa - Dedi Holden simbolon (BULLET : Jurnal Multidisiplin Ilmu, 2022)
−The quality of learning can be seen from the relationship between the ability of lecturers in carrying out learning and the learning climate to produce optimal student learning processes and outcomes in accordance with the demands of the current curriculum. Case Based Learning (CBL) is one of the learning methods for Student Center Learning (SCL). The purpose of this study was to analyze the effect of the application of the CBL model on student learning outcomes. This research is a quantitative Quasi experiment with a Pretest-Posttest Control approach with a control group. The samples taken were 32 experimental class and 31 control class using Simple Random Sampling technique. The results showed that there was a significant effect on student learning outcomes after the CBL model was applied. The CBL model is one of the innovative and effective methods in developing student knowledge in learning so as to obtain better learning outcomes